2014
DOI: 10.4067/s0301-732x2014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Paratuberculosis or avian tuberculosis in red deer with chronic diarrhea?

Abstract: SUMMARYMycobacterium avium subsp. paratuberculosis (Map) is the etiological agent of paratuberculosis. In Chile, information about Map isolation from both domestic ruminant and wildlife species has been accumulating, but it has extended to other species. In Chile, deer farming activity has been focused in hunting and meat production. No paratuberculosis surveillance has been reported for these source herds. In the present study, chronic diarrhea and poor body condition in some animals belonging to a deer farm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
1
6
0
1
Order By: Relevance
“…Macroscopic lesions were observed mainly in the small intestine (jejunum and ileum) and mesenteric LN. Thickening of the intestinal wall and increase on the size of LN was the most commonly observed feature, consistent with the findings of Balseiro et al (2008) and Pradenas et al (2014). Williams et al (1983) also coincides with the macroscopic findings in the LN, but reports that the intestine maintains a normal appearance without macroscopic alterations.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Macroscopic lesions were observed mainly in the small intestine (jejunum and ileum) and mesenteric LN. Thickening of the intestinal wall and increase on the size of LN was the most commonly observed feature, consistent with the findings of Balseiro et al (2008) and Pradenas et al (2014). Williams et al (1983) also coincides with the macroscopic findings in the LN, but reports that the intestine maintains a normal appearance without macroscopic alterations.…”
Section: Discussionsupporting
confidence: 71%
“…Del-Pozo et al (2013) describes an unusual case of paratuberculosis in which multifocal granulomas were found in random arrangement within the parenchyma. Very few authors reported liver damage in paratuberculosis (Mahmoud et al 2002, Paredes et al 2007, Pradenas et al 2014, probably because it is not considered a site of predilection for the disease. Only 3 animals showed AFB in the liver (cases 3.5 and 15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infections with MAP have also been reported in introduced deer species in southern Chile, such as the red deer Infectología al Día (Cervus elaphus) and fallow deer (Dama dama), which could be transmitting the pathogen to livestock and vice versa 72,73 . The European wild boar (Sus scrofa) is currently distributed in rural and protected areas of south-central Chile and is considered as a carrier of MAP in Europe 74,75 .…”
Section: Mycobacteriummentioning
confidence: 99%